Archaeolinguistic evidence for the farming/language dispersal of Koreanic. (14th October 2020) - Hudson, Mark J.; Robbeets, Martine
Abstract: Abstract: While earlier research often saw Altaic as an exception to the farming/language dispersal hypothesis, recent work on millet cultivation in northeast China has led to the proposal that the West Liao basin was the Neolithic homeland of a Transeurasian language family. Here, we examine the archaeolinguistic evidence used to associate millet farming dispersals with Proto-Macro-Koreanic, analysing the identification of population movements in the archaeological record, the role of small-scale cultivation in language dispersals, and Middle–Late Neolithic demography. We conclude that the archaeological evidence is consistent with the arrival and spread of Proto-Macro-Koreanic on the peninsula in association with millet cultivation in the Middle Neolithic. This dispersal of Proto-Macro-Koreanic occurred before an apparent population crash after 3000 BC, which can probably be linked with a Late Neolithic decline affecting many regions across northern Eurasia. We suggest plague ( Yersinia pestis ) as one possible cause of an apparently simultaneous population decline in Korea and Japan.